A New Approach to Evaluate Neuromuscular Fatigue of Extensor Elbow Muscles - Norberto, Matheus Silva; de Arruda, Tarine Botta; Papoti, Marcelo (Frontiers in Physiology, 2020)
Neuromuscular evaluation is widely performed on different muscles through the muscle stimulation in addition to maximum voluntary contraction (MVC). Considering the possible co-contraction effects from of biceps on triceps brachii during muscular stimulations, the aim of this study was to assess a new approach of neuromuscular fatigue protocol evaluation on elbow extensor musculature. Twenty participants preformed exercises to induce central (CenFat) and peripheral fatigue (PerFat). Neuromuscular fatigue was evaluated on lower limbs by a reliable knee extensor muscles protocol that’s provides Twitch Superimposed (TSK) and Twitch Potentiated (TPK), central and peripheral parameters respectively. This new approach for elbow extensor muscles used sustained submaximal contraction at 10, 20, 30, 40 and 50% of maximum voluntary contraction (MVC). The neuromuscular fatigue in upper limbs was identified by Twitch Control (TCE) and multiples Twitch Superimposed (TSE). The propose protocol used several TSE to provides slope, y-intercept and R² by the relationship between MVC (%) and evoked force. It is proposed that slopes change may indicate central fatigue, the relationship between y-intercept and R² identify peripheral fatigue and distinguishes the naturalness of fatigue (central or peripheral). The results were compared using the non-parametric analyzes of Friedmann and Wilcoxon and their possible correlations were verified by the Spearmann test (significance level set at p <0.05). After PerFat was found decrease in TCE (42,8%, p <0,001) but not in TSE, indicating only peripheral fatigue by upper limbs. After CenFat was found decrease in TCE (78,5%, p: 0,008) and TPK (78,8%, p <0,001) but not in TSK, indicating peripheral fatigue in upper and lower limbs but not central fatigue. A slight, but not significant, increase of 15.3% after CenFat and a statistical reduction (80,1%, p: 0,001) after PerFat were found by slope. Differences after exercise were also found for R², showing recovery (10min) only after central fatigue exercise (p: 0.016). The PerFat fulfilled its purpose and provide only peripheral fatigue. The CenFat protocol did not provide central fatigue. Considering the procedural limitations of the exercises used, parameters resulting from the proposed protocol are sensitive to neuromuscular alteration, however, further studies are required.